English-medium education in internationalised universities: sketching a way forward: Introduction to the special issue. Issue 2 (1st October 2021) - Studer, Patrick; Smit, Ute
Abstract : The increasing use of English as a medium of education (EME) in higher education has attracted an impressive amount of applied linguistic research, reflecting the pivotal role language plays in teaching and learning processes. This, however, stands in sharp contrast to the equally prolific body of research into the internationalisation of higher education (IoHE) in which the complex linguistic reality of EME – and its potential role in the internationalised classroom – is given little attention. Reviewing the current research and policy agenda, the authors find that the current policy climate offers similar opportunities for conceptual expansion of IoHE and EME, which calls for greater integration of the two fields of study. The authors argue for an interdisciplinary approach, recognising, and more holistically exploiting, the potential of language at the intersection of dynamic and multilayered policies and practices in twenty-first century internationalised higher education.